2017
DOI: 10.1371/journal.pone.0184624
|View full text |Cite
|
Sign up to set email alerts
|

Experimental colitis delays and reduces the severity of collagen-induced arthritis in mice

Abstract: Amongst extraintestinal manifestations (EIM) occurring in IBD patients, rheumatologic manifestations are the most frequent. Understanding the relationships between arthritis and colitis is a prerequisite to improving the management of these patients. Microbiota of patients with IBD or rheumatologic diseases, like spondyloarthritis (SpA) is modified compared to healthy individual. Thus, we have evaluated the impact of colitis in the development of arthritis in mice and we have analyzed microbiota changes. Colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Gevers et al [59] reported G. moribillum to be present in higher abundance in CD compared to controls. Interestingly, a recent experimental colitis study has reported that Gemella , in addition to Ruminococcus and Blautia, were overrepresented in the arthritis and colitis group versus arthritis only, at 41 days post-induction [61]. There are numerous environmental and genetic risk factors that are known to influence IMID.…”
Section: Discussionmentioning
confidence: 99%
“…Gevers et al [59] reported G. moribillum to be present in higher abundance in CD compared to controls. Interestingly, a recent experimental colitis study has reported that Gemella , in addition to Ruminococcus and Blautia, were overrepresented in the arthritis and colitis group versus arthritis only, at 41 days post-induction [61]. There are numerous environmental and genetic risk factors that are known to influence IMID.…”
Section: Discussionmentioning
confidence: 99%
“…The decalcified tissues were embedded in paraffin, and sectioned 5 μm and stained with hematoxylin and eosin. The histological arthritis score was determined in a blinded manner for changes in synovial inflammation, cartilage degradation, and bone erosion as previously described(Ishikawa et al, 2016; Hablot et al, 2017). Synovial inflammation was scored as following scale: 0 = normal, 1 = slight thickening of the lining layer with some infiltrating cells in the sublining layer, 2 = moderate thickening of the lining layer with a moderate number of infiltrating cells in the sublining layer, 3 = severe inflammation with a massive immune cell infiltrate into the synovium.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the abundance of Prevotella copri is increased in some patients with early-stage RA, but Prevotella histicola from the human gut microbiota suppresses the development of RA [58]. Interestingly, Hablot et al evaluated the impact of experimental colitis on the development of CIA in mice and observed that concomitant experimental colitis reduced severity in association with modification of the gut microbiota composition [59].…”
Section: The Gut Microbiota and Autoimmune Diseasesmentioning
confidence: 99%